2015
DOI: 10.1371/journal.pone.0123286
|View full text |Cite
|
Sign up to set email alerts
|

“They Know, They Agree, but They Don’t Do”- The Paradox of Tuberculosis Case Notification by Private Practitioners in Alappuzha District, Kerala, India

Abstract: BackgroundDespite being a recognized standard of tuberculosis (TB) care internationally, mandatory TB case notification brings forth challenges from the private sector. Only three TB cases were notified in 2013 by private practitioners compared to 2000 TB cases notified yearly from the public sector in Alappuzha district. The study objective was to explore the knowledge, opinion and barriers regarding TB Notification among private practitioners offering TB services in Alappuzha, Kerala state, India.Methods & F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
53
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(70 citation statements)
references
References 13 publications
9
53
1
Order By: Relevance
“…Our findings are indicative of an urgent need to educate PPs systematically about TB notification and to improve the TB notification system, as has also been recommended by Philip et al 16 In our study, issues regarding ethics, confidentiality and the notification process itself emerged from PP interviews. These areas could all be addressed by training PPs in TB notification by RNTCP staff.…”
Section: Discussionsupporting
confidence: 68%
“…Our findings are indicative of an urgent need to educate PPs systematically about TB notification and to improve the TB notification system, as has also been recommended by Philip et al 16 In our study, issues regarding ethics, confidentiality and the notification process itself emerged from PP interviews. These areas could all be addressed by training PPs in TB notification by RNTCP staff.…”
Section: Discussionsupporting
confidence: 68%
“…Raising awareness, collection of notification forms right at PP clinics and constant dialogue between RNTCP staff and PPs had no effect on notification in our study. Studies trying to understand the barriers to notification in India reported that not all PPs have fully understood the notification's rationale and that, although aware, many do not notify, the main reasons being lack of time, concerns regarding patients’ confidentiality and lack of trust in the government health system . Ensuring notification without legal backup seems difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the evidence base of PPM effectiveness is considered rather weak and several unknowns remain regarding initiatives to effectively and sustainably engage PPs . In India, since 2012 it is mandatory for PPs to notify TB cases diagnosed outside RNTCP but notifications remain low .…”
Section: Introductionmentioning
confidence: 99%
“…Such an effort is expected to increase the overall number of notified cases to the RNTCP, thereby presenting a correct picture of the actual TB burden in the community. Sairu Philip and colleagues have recognized that notification of TB as a public health measure for control of TB needs to be showcased to the private practitioners in India [19]. …”
Section: Discussionmentioning
confidence: 99%